Streamer interaction and consumer impulsive buying in live-stream commerce: the mediating roles of trust and emotional arousal with anticipated regret as boundary condition - Wang, Chengmin; Chen, Baohua; Hu, Shoufeng; Li, Jiahui (Frontiers in Communication, 2025)
IntroductionOnline shopping’s convenience often drives impulsive buying, yet the associated regret emotions pose challenges for consumer satisfaction and businesses’ long-term customer relationship management. This study investigates how streamer interaction orientation influences impulsive buying intentions through cognitive trust and emotional arousal, incorporating anticipated regret as a moderating factor.MethodsGrounded in cognitive-affective system theory and regret theory, this study analyzes 503 screened responses using structural equation modeling and the Bootstrap method to examine the relationships among streamer interaction orientation, cognitive trust, emotional arousal, anticipated regret, and impulsive buying intentions.ResultsThe findings reveal that anticipated regret significantly amplifies the direct effects of cognitive trust and emotional arousal on impulsive buying intentions. Additionally, cognitive trust and emotional arousal mediate the relationship between streamer interaction orientation and impulsive buying intentions, with their mediating roles strengthened by anticipated regret.DiscussionThis study introduces a novel moderated dual-mediation model, enriching the theoretical understanding of impulsive buying antecedents. It extends the application of anticipated regret in consumer behavior and provides actionable insights for optimizing marketing strategies and consumer experiences in live-streamed e-commerce.